Psycho-demographic predictors of academic achievement motivation among secondary school adolescents in Ibadan metropolis (2014)
This study investigated the predictive influence of self-esteem, academic optimism, attribution style, age and gender on academic achievement motivation among adolescents in schools of science in Ibadan metropolis. The study adopted a descriptive survey research design. A sample of two hundred and eighty seven participants was randomly selected from three secondary schools drawn from three local government areas within Ibadan Metropolis. The participants comprised 187 male and 100 female and the age range was between 12 to 21 years, with mean age of 16.05. Data was subjected to Pearson’s Product Moment Correlation and Multiple Regressions analysis. The result revealed that each of the independent variables have significant relationship with academic achievement motivation of secondary school students. However, gender made no relative contribution to the dependent variable. The study has implications for all educational stakeholders such as students, teachers, parents and counselling psychologists. It however suggested the need for counselling psychologists to assist students develop self affirmative attitude in order to boost their self-esteem, encourage optimistic disposition and take responsibility for their academic successes